2016
DOI: 10.21315/tlsr2016.27.3.21
|View full text |Cite
|
Sign up to set email alerts
|

Psychrophilic Lipase from Arctic Bacterium

Abstract: A lipase producer psychrophilic microorganism isolated from Arctic sample was studied. The genomic DNA of the isolate was extracted using modified CTAB method. Identification of the isolate by morphological and 16S rRNA sequence analysis revealed that the isolate is closely related to Arthrobacter gangotriensis (97% similarity). A. gangotriensis was determined as positive lipase producer based on the plate screening using specific and sensitive plate assay of Rhodamine B. The PCR result using Arthrobacter sp.'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Lipase-producing potentiality was investigated based on the size of the clear zone around each colony (Ramle and Abdul Rahim, 2016). Results indicated that all isolates were positive producers of lipase with different efficiency as the lipolytic zone diameter range was 6–20 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Lipase-producing potentiality was investigated based on the size of the clear zone around each colony (Ramle and Abdul Rahim, 2016). Results indicated that all isolates were positive producers of lipase with different efficiency as the lipolytic zone diameter range was 6–20 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Psychrotolerants are organisms that can withstand a broader range of temperatures between 0 °C to approximately 36 °C [25]. Some researchers called them facultative psychrophiles or psychrotrophs and their maximal or optimal growth temperature was above 20 ºC [26,27]. Based on the OFAT, all isolated strains showed the fastest growth rate at 20 °C.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial isolate was obtained from an Artic soil sample, ARC4, collected by the Polar Research Group of Universiti Sains Malaysia (USM) ( 87 ). The sampling took place in August 2011, on the northern coast of Hornsund, Wedel Jarlsberg Land, West Spitsbergen ( o 00′04″N, 15°33′37″E).…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial isolate was cultivated in Luria-Bertani (LB) agar plates at different temperatures: 15°C, 24°C, and 37°C for 48 h to test whether the isolate fit the definition of obligate psychrophile or facultative psychrotroph ( 87 ). Obligate psychrophiles are organisms that prefer temperatures close to 0 for growth ( 70 ).…”
Section: Methodsmentioning
confidence: 99%